Evaluating Digital Learning Media: Impact of Synchronous and Asynchronous Approaches in IT - Harleni Harleni; Andhika Herayono; Fahmi Rizal; Ambiyar; Rijal Abdullah (Komunitas Dosen Indonesia, 2025)
This study critically evaluates the effectiveness and relevance of synchronous and asynchronous learning media using a meta-analysis approach, aiming to provide a deeper understanding of their role in the rapidly evolving post-pandemic educational landscape. The unprecedented acceleration of online learning due to COVID-19 has highlighted the need for rigorous evaluation of digital media to ensure that educational delivery remains effective, equitable, and sustainable. Synchronous learning, characterized by real-time interaction, and asynchronous learning, which allows flexible and self-paced engagement, have become indispensable components of modern education. To conduct this analysis, 26 peer-reviewed articles were systematically selected and analyzed using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, with studies categorized by research type, education level, and methodology to ensure quality and relevance. The findings indicate that both synchronous and asynchronous media significantly improve learning effectiveness, particularly by enhancing student engagement, accessibility, and adaptability to diverse learning needs. For educators, these results highlight the necessity of designing blended learning strategies that balance real-time interaction with flexible content access. For students, the combined use of these media fosters personalized learning experiences, supporting both collaboration and autonomy. At the institutional level, the findings emphasize the importance of investing in robust digital infrastructures and pedagogical innovations to remain responsive to future disruptions. Funnel plot analysis confirms minimal publication, reinforcing the reliability of the findings. This study provides actionable recommendations for educators and policymakers to strategically integrate synchronous and asynchronous learning methods, shaping more inclusive and resilient educational framework for the digital era.